Digital Transformation in Islamic Higher Education: E-Learning and Visionary Leadership at UIN Siber Syekh Nurjati Cirebon - Suhatma Suhatma; Ade Aspandi; Mukhlisoh Mukhlisoh (Sakura Digital Nusantara, 2026)
Purpose: This study aims to analyze the implementation of digital transformation management through e-learning optimization and visionary leadership at Universitas Islam Negeri Siber Syekh Nurjati Cirebon as an effort to strengthen the quality, effectiveness, and competitiveness of Islamic higher education in the digital era. Methods: This study employed a qualitative case study approach. Data were collected through semi-structured interviews with key stakeholders involved in the university’s digital transformation process and supported by institutional documentation, including strategic plans, digital transformation policies, and academic governance reports. Informants were selected purposively based on their direct involvement in planning, implementing, and evaluating digital transformation initiatives. Data credibility was ensured through source triangulation and document verification, while data analysis followed the interactive model of data reduction, data display, and conclusion drawing. Findings: The study found that digital transformation at Universitas Islam Negeri Siber Syekh Nurjati Cirebon has been implemented through the strengthening of digital infrastructure, optimization of the SPADA-based e-learning system, digitalization of academic services, and the development of a collaborative digital culture. The findings further indicate that visionary leadership has played a strategic role in formulating digital policies, encouraging institutional adaptation, and fostering stakeholder participation in transformation processes. Nevertheless, several challenges remain, including disparities in digital competencies among lecturers and students, limitations in technological infrastructure, and resistance to organizational change. The interaction between digital innovation and leadership commitment has become a key factor in sustaining institutional transformation. Research Implications: The findings provide practical insights for Islamic higher education institutions in designing sustainable digital transformation strategies through the integration of digital learning systems, capacity-building programs, and adaptive leadership practices. Originality: This study contributes to the growing literature on digital transformation in Islamic higher education by demonstrating how e-learning optimization and visionary leadership interact in supporting institutional transformation within a cyber-based university environment grounded in Islamic educational values.